2022
DOI: 10.5603/rpor.a2022.0055
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of radiation-induced hypothyroidism following head and neck irradiation: a single-center analysis

Abstract: Background:The purpose of this study was to investigate the incidence of primary hypothyroidism (HT), as well as any correlation between dosimetric parameters and thyroid dysfunctions after neck radiotherapy (RT) in head and neck cancer (HNC) patients. Materials and methods:This study retrospectively reviewed HNC patients who finished neck RT for at least 12 months and who had available back-up treatment information. Eligible patients further received a single thyroid function test (TFT). Dosimetric parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Lee et al analyzed 149 patients with NPC and showed that age has no significant effect upon RIHT [ 14 ]. Several researches also believed that age’s effect upon RIHT is not significant, which was consistent to our study [ 15 , 16 ]. However, in Diaz et al’s research, the risk for increasing age were 0.93 [ 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…Lee et al analyzed 149 patients with NPC and showed that age has no significant effect upon RIHT [ 14 ]. Several researches also believed that age’s effect upon RIHT is not significant, which was consistent to our study [ 15 , 16 ]. However, in Diaz et al’s research, the risk for increasing age were 0.93 [ 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…This study showed that 40.6% of patients developed hypothyroidism. The same study demonstrated that when the volume of the thyroid spared from radiation therapy was more than 5 cm 3 , the risk of hypothyroidism decreased [ 74 •].…”
Section: Thyroid Complications Of Radiation Fibrosis Syndromementioning
confidence: 99%